Broad spectrum antibacterial zinc oxide-reduced graphene oxide nanocomposite for water depollution. (January 2023) - Rajapaksha, P.; Orrell-Trigg, R.; Shah, D.; Cheeseman, S.; Vu, K.B.; Ngo, S.T.; Murdoch, B.J.; Choudhury, N.R.; Yin, H.; Cozzolino, D.; Truong, Y.B.; Lee, A.F.; et al.
Abstract: Antimicrobial-resistance (AMR) is a global health challenge arising from the evolution of bacteria, viruses, fungi, and parasites, such that pathogenic microorganisms no longer respond to classical therapies. AMR and the rise of so-called 'superbugs' requires innovative nanomaterials and biostatic strategies. Here we report a broad spectrum, antimicrobial nanomaterial integrating light-responsive ZnO nanoparticles (NP) and reduced graphene oxide (rGO) into a heterojunction semiconductor nanocomposite for water depollution. Simultaneous chemical reduction of Zn sulphate and GO sheets yields a low concentration (0.5 mol%) of 10 nm ZnO nanoparticles decorating fragmented rGO nanosheets, with a total surface area of 12 m 2 /g and optical band gap of 1.6 eV. Antimicrobial performance of the ZnO-rGO nanocomposite was evaluated against methicillin-resistant Staphylococcus aureus (MRSA), Escherichia coli 0157:H7 and Salmonella typhimurium bacteria, which are prevalent in contaminated aquatic systems; antimicrobial efficacy against these organisms was 96%, 97%, and 73%, respectively, for a loading of 2 mg/mL, evidencing a strong synergy compared with pure ZnO or rGO components. ZnO-rGO was also an effective photocatalyst for the aqueous degradation of Malachite Green dye, suggesting that its mode of antibacterial action reflects the production of reactive oxygen species under ambient illumination. Highlights: A nanocomposite comprising ZnO nanoparticles and wrinkled reduced graphene oxide (rGO) sheets was synthesised. A synergy between ZnO and rGO components was demonstrated towards waterborne Gram-negative and -positive bacteria. A photocatalytic bactericidal mechanism is invoked involving the generation of reactive oxygen species.